Strategy for Revitalizing the Role of Islamic Religious Education Teachers in Overcoming Bullying Behavior at North Luwu Vocational High School - S, Sumarni; Rustan, Edhy; Zainuddin, Fauziah (Universitas Nusantara PGRI Kediri, 2023)
This research begins with the observation that we saw at SMKN North Luwu City that we found that there was quite a high incidence of physical bullying by students there. So that made us conduct research that aims to find out what forms of physical bullying behavior are carried out by students, what are the strategies of PAI teachers in dealing with physical bullying behavior in students and want to know what are the obstacles and solutions in dealing with these problems. This research uses a descriptive qualitative research type. The subjects in this study were PAI teachers and their supporting informants were school principals, student assistants, counseling teachers, teachers, security guards and students. This study used data collection techniques by observation, interviews with informants and documentation. To check the validity of the data obtained, we use a triangulation technique by re-collecting data if there is unclear data. Based on the data obtained, the following research results were found, namely forms of bullying by children such as pushing a friend's body, kicking, hitting, pushing the head, and so on. There are two strategies used by PAI teachers in dealing with bullying behavior physically, first by using the lecture strategy, namely giving directions and advice to students.